2020
DOI: 10.1038/s41598-020-76638-6
|View full text |Cite
|
Sign up to set email alerts
|

Lufenuron induces reproductive toxicity and genotoxic effects in pregnant albino rats and their fetuses

Abstract: Insecticides and other agrochemicals have become indispensable components of the agricultural system to ensure a notable increase in crop yield and food production. As a natural consequence, chemical residues result in significantly increased contamination of both terrestrial and aquatic ecosystems. The present study evaluated the teratogenic, genotoxic, and oxidative stress effects of residual-level lufenuron exposure on pregnant rats during the organogenesis gestational period of both mother and fetus. The t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 105 publications
5
13
0
1
Order By: Relevance
“…In addition, severe hepatotoxicity has been reported to induce hepatoencephalopathic neurobehavioral alterations (Hayase et al 2000) The results of the present study revealed that IC and HFM induced hepatorenal oxidative stress damage manifested by increased MDA levels and decreased TAC levels associated with the upregulation of HO-1 gene and down-regulation of Keap1 gene levels. These ndings agreed with other report showed that lufenuron, belonging to the same hexa umuron-family, was able to induce oxidative stress damage in the liver of rats (Basal et al 2020). Also, chronic exposure to IC alters in ammation and oxidative stress markers…”
Section: Discussionsupporting
confidence: 93%
“…In addition, severe hepatotoxicity has been reported to induce hepatoencephalopathic neurobehavioral alterations (Hayase et al 2000) The results of the present study revealed that IC and HFM induced hepatorenal oxidative stress damage manifested by increased MDA levels and decreased TAC levels associated with the upregulation of HO-1 gene and down-regulation of Keap1 gene levels. These ndings agreed with other report showed that lufenuron, belonging to the same hexa umuron-family, was able to induce oxidative stress damage in the liver of rats (Basal et al 2020). Also, chronic exposure to IC alters in ammation and oxidative stress markers…”
Section: Discussionsupporting
confidence: 93%
“…Epigenetic changes are necessary to direct normal cellular development and differentiation in developing organisms, however, developmental abnormalities may occur in response to inappropriate epigenetic signaling [ 76 ]. Besides, maternal exposure to lufenuron, an insecticide, during organogenesis had caused glomerular shrinkage in the progenies, which might be due to the genotoxic stress and cell cycle arrest of this insecticide [ 77 ]. This might explain the possible mechanism involved in the paternal exposure of FNT, which caused glomerulus shrinkage in the male F1 progeny rats.…”
Section: Discussionmentioning
confidence: 99%
“…Thiacloprid-based insecticide treatment resulted in p53-mediated cell cycle arrest at the G0/G1 phase, and apoptosis induction in bovine lymphocytes (Schwarzbacherová et al, 2019). In a more recent study carried out in our labs, exposure of pregnant albino rats to lufenuron during the organogenesis period led to cell cycle arrest in liver cells of both mothers and fetuses at the G0/G1 phase (Basal et al, 2020).…”
Section: Discussionmentioning
confidence: 78%
“…It also interfered with the formation of spindle fibers in spermatid cells of mice (Deivanayagam et al, 2013) along with the induction of molecular lesions in the mice genome (Abou Gabal, 2006). At the DNA level, comet assay revealed significant damage in hepatocytes of female rats and their fetuses (Basal et al, 2020), fruit fly (Eid et al, 2017) and freshwater snails (Ibrahim et al, 2018) after treatment with lufenuron. The same results were obtained in vivo after treatment of mice peripheral blood lymphocytes to carbofuran (Pei et al, 2005).…”
Section: Discussionmentioning
confidence: 99%